2004
DOI: 10.1001/archneur.61.10.1590
|View full text |Cite
|
Sign up to set email alerts
|

Is Posttraumatic Benign Paroxysmal Positional Vertigo Different From the Idiopathic Form?

Abstract: The nature and severity of the traumas causing t-BPPV are diverse, ranging from minor head injuries to more severe head and neck trauma with brief loss of consciousness. It appears that t-BPPV is more difficult to treat than i-BPPV, and also has a greater tendency to recur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
5
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 23 publications
9
130
5
6
Order By: Relevance
“…For dizziness occurring at times other than in bed, cervicogenic vertigo must be considered after a whiplash trauma. Head injury may equally affect both labyrinths; thus, bilateral BPPV is expected to occur more frequently in the posttraumatic cases [35,39], although we have not noted a high incidence of bilateral cases in our series.…”
Section: Discussioncontrasting
confidence: 54%
“…For dizziness occurring at times other than in bed, cervicogenic vertigo must be considered after a whiplash trauma. Head injury may equally affect both labyrinths; thus, bilateral BPPV is expected to occur more frequently in the posttraumatic cases [35,39], although we have not noted a high incidence of bilateral cases in our series.…”
Section: Discussioncontrasting
confidence: 54%
“…In a recent prospective study with 247 patients, Gordon et al reported that trauma resulting BPPV cases are much less frequent than idiopathic origin BPPV cases (8.5% in this study are trauma-related), they are, however, more difficult to treat, requiring repeated treatment sessions to completely resolve the symptoms (77% vs 14%, respectively, p<0.001), besides having greater recurrence trends (57% vs 19%, respectively, p<0.004) 37 .…”
Section: Discussionmentioning
confidence: 47%
“…173 Patients with BPPV after trauma are likely to demonstrate an even higher recurrence rate of their BPPV. 132 Thus, clinicians should be aware of the recurrence risk of BPPV and should counsel patients accordingly. Counseling will likely have several benefits.…”
Section: Action Statement Profile For Statementmentioning
confidence: 99%